HARRY N. SCHEIBER / LAURENT MAYALI (eds.), Emerging Concepts of Rights in Japanese Law - Baum, Harald (Zeitschrift für Japanisches Recht, 2008)
HARRY N. SCHEIBER / LAURENT MAYALI (eds.) Emerging Concepts of Rights in Japanese Law The Robbins Collection, School of Law (Boalt Hall) University of Californiaat Berkeley, 2007; ix + 230 S.; US 40.-; ISBN 978-1-882239-17-7